Typology of the areas of influence of the Primary Health Care Centers in the city of Lujan, Province of Buenos Aires, Argentina (Huellas, 2016)
Quantitative methods used through Geographical Information Systems (GIS) are extremely useful for the treatment of geographic information in Applied Geography studies. A combination of these possibilities is applied in the field of Health Geography to study the spatial distribution of population and health care services. The aim of this paper is to define and analyze the areas of influence of Primary Health Care Centers (PHCC) in the city of Lujan (Province of Buenos Aires) as the basis of health socio-spatial system.
Keywords: Health Geography; Health Services Geography; Primary Health Care Center; Area of Influence; Geographical Information Systems.